Pengurusan Izin Kedatangan dan Keberangkatan Kapal pada PT. Admiral Lines Cabang Belawan - Helmi Trinisa Br. Sinulingga; Fadiyah Hani Sabila; Masringgit Marwiyah Nst (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
PT. Admiral Lines Belawan Branch is a company that operates owned vessels and is also engaged in agency services. In the sense of representative of the ship owner / principle for processing documents at the port for both arrival and departure of the ship. Ports as arrival and departure terminals for ships and cargo need to provide adequate facilities and services so that ships can be served smoothly and efficiently. Managing the arrival and departure of a ship more smoothly and efficiently cannot be separated from an application called the INAPORNET system. The position of the port as the gateway for a ship entering/leaving the port, especially from within the country or abroad or vice versa, must obtain approval from the authorized agencies at the port, such as the Harbor Master's Office and Port Authority (KSOP), Health Quarantine, Customs and Excise, Immigration. This notification is to ensure that the ship and its cargo entering/exiting the port have complied with the provisions of applicable laws and conventions. Management of the needs and interests of ships and their cargo is carried out by shipping company branches such as PT. Belawan Branch Line Admiral. In writing this paper the author used methods, literature and the internet.